A CASE OF IDIOPATHIC PERFORATION OF THE SMALL INTESTINE - MORI, Hideki; HAYASHI, Ken; KUSAKABE, Teruo; SUZUKI, Yasushi; TSUSHIMA, Hidehumi; DATE, Yuko (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2006)
We present a case of idiopathic perforation of the small intestine with a review of 38 case reports in Japan. An 83-year-old woman visited our hospital because of lumbago, and after medical treatment returned home. But she revisited the same day because of no improvement of the lumbago and was then admitted for observation of her clinical course. The next morning, abdominal X-ray films revealed right subphrenic free air, and endoscopic examination upper digestine that revealed no special lesion. An emergency laparotomy was performed with a diagnosis of perforation of the large intestine. At the laparotomy, the perforation was confirmed at the ileum, located 80cm from Bauhin's valve. A partial ilial resection including the perforated lesion measuring about 25cm was then performed. Histologically, the mucosa, muscle and serosa layer were completely cleft, and special lesions were not seen around the perforated lesion. The cause of the perforation was not specified from any findings, and the patient was definitely diagnosed with idiopathic small bowel perforation. The postoperative course was good, and she was discharged on the 61th postoperative day.